A suggested proposal to increase social institutions to strengthen the culture of caring for the elderly: “A study applied to the Mabarrat Al-Muslimeen Association for the Care of the Elderly” Port Said Governorate - Arab Republic of Egypt - Noufal, Zezit Mostafa Abdou (Al-Adab Journal, 2022)
The elderly suffers from many problems that contribute to a feeling of social and psychological insecurity, as they are dominated by the fear associated with increasing age, and the lack of appropriate methods for integrated care. The study is aimed to explain the reasons for the problem of family abandonment for elderly care, to determine the effects resulting from families abandoning their care for the elderly, specify the programs of social institutions to strengthen the culture of care for the elderly, identify the obstacles facing the provision of social programs for the elderly in shelters, and finally arrive at a proposed vision to increase the effectiveness of social programs for the elderly in shelters. This descriptive analytical study’s methodology is built on a comprehensive social survey.